Pleiotropic Effects of Suppressor Mutations in Bacillus subtilis - Tevethia, M. J. (1974)
Isogenic strains of Bacillus subtilis carrying sup-1 (26), sup-3 (10), or their wild-type alleles were constructed in three genetic backgrounds. The patterns of suppression at 37 and 43.5 C, identity of mapping site, effects of the suppressor genes on growth rate, sporulation, and production of altered enzymes were examined. The similarity of the suppression pattern by sup-1 and sup-3 suggests that the suppressors are of the same type. They do not, however, represent mutations in the same gene, since, based on differences in temperature sensitivity of phage mutants in suppressor-containing hosts, sup-1 and sup-3 insert different amino acids and can coexist within the same cell. The ability to produce slow-migrating forms of enzymes of the type described in the accompanying paper was co-transferred with either of the suppressor genes during transformation, was lost on reversion of the suppressor mutations, and was independent of the genetic background. Similarly, transformation and reversion studies indicate that the additional pleiotropic properties such as slow growth rate and inability to attain competence or to yield plaques with φ105C4, which are characteristic of the Okubo sup-1 strain (HA101B) but not its early sporulation defect, result from the presence of the suppressor mutation. The possible mechanisms by which altered enzyme forms and the additional pleiotropic effects are produced in suppressor strains are discussed. In addition, a newly recognized suppressor phenotype is described and partially characterized.